2010
DOI: 10.1124/mol.110.064295
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor Transmembrane Mutations Convert Ivermectin from a Positive to a Negative Allosteric Modulator

Abstract: Ivermectin is a macrocyclic lactone that acts as a positive allosteric modulator of ␣7 nicotinic acetylcholine receptors (nAChRs) but has no modulatory activity on 5-hydroxytryptamine (5-HT) type 3 (5-HT 3 ) receptors. By examining the influence of ivermectin on subunit chimeras containing domains from the nAChR ␣7 subunit and the 5-HT3A subunit, we have concluded that the transmembrane domains play a critical role in influencing allosteric modulation by ivermectin. A series of mutations located within the ␣-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 40 publications
3
88
0
Order By: Relevance
“…As has been demonstrated previously, MLA causes a surmountable block of acetylcholine-evoked responses (22,26). Here, MLA was found to act as a reversible antagonist of responses evoked by 4BP-TQS (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…As has been demonstrated previously, MLA causes a surmountable block of acetylcholine-evoked responses (22,26). Here, MLA was found to act as a reversible antagonist of responses evoked by 4BP-TQS (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…In previous studies (21) we have identified an intrasubunit cavity, located between the four transmembrane α-helices, as the allosteric binding site for both type I and type II PAMs acting on α7 nAChRs (21,22). Here, we provide evidence that ligand binding at this transmembrane allosteric site is able to activate nAChRs in the absence of agonist binding at the orthosteric site.…”
mentioning
confidence: 49%
See 3 more Smart Citations